2014
DOI: 10.1016/j.neuroimage.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Functional organization of human auditory cortex: Investigation of response latencies through direct recordings

Abstract: The model for functional organization of human auditory cortex is in part based on findings in non-human primates, where the auditory cortex is hierarchically delineated into core, belt and parabelt fields. This model envisions that core cortex directly projects to belt, but not to parabelt, whereas belt regions are a major source of direct input for auditory parabelt. In humans, the posteromedial portion of Heschl’s gyrus (HG) represents core auditory cortex, whereas the anterolateral portion of HG and the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
86
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 89 publications
(113 citation statements)
references
References 70 publications
(118 reference statements)
26
86
1
Order By: Relevance
“…On average, peak activity occurred on the falling phase of the N α peak of the AEP, consistent with earlier findings (Steinschneider et al, 2011). Sources of variability likely include differences in sensitivity of different cortical sites to specific acoustic attributes of speech sounds and tones, state of arousal of the subject during the passive-listening paradigm, differences in electrode coverage and response timings within PLST (Nourski et al, 2014a). In the latter study, high gamma activity was shown to have the shortest onset latency in the middle portion of PLST, increasing in both anterior and posterior directions along the gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…On average, peak activity occurred on the falling phase of the N α peak of the AEP, consistent with earlier findings (Steinschneider et al, 2011). Sources of variability likely include differences in sensitivity of different cortical sites to specific acoustic attributes of speech sounds and tones, state of arousal of the subject during the passive-listening paradigm, differences in electrode coverage and response timings within PLST (Nourski et al, 2014a). In the latter study, high gamma activity was shown to have the shortest onset latency in the middle portion of PLST, increasing in both anterior and posterior directions along the gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…Sites on HG were subdivided into core (posteromedial) and non-core (anterolateral) areas based on the morphology and latency of evoked responses and frequency following responses to click train stimuli (Brugge et al, 2008; Nourski et al, 2014). While separate statistical analysis of core and non-core areas of HG was not possible due to the small number of recording sites, we do present an exploratory analysis comparing these two subdivisions.…”
Section: Methodsmentioning
confidence: 99%
“…We used this approach rather than an individual site-by-site analyses or area-wide ANOVAs for several reasons (see also Nourski et al, 2014). First, site-by-site analyses offer no way to account for the fact that the sites only come from a small number of participants (instead, each site is treated as an independent measure [analogous to an independent subject]).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations